Fall Panicum: Biology and Control in Sugarcane - Curtis Rainbolt; Brent Sellers (EDIS, 2006)
SS-AGR-132, a 3-page illustrated fact sheet by Curtis Rainbolt and Brent Sellers, is part of the Sugarcane Handbook. It describes the biology and identification and control in sugarcane of this native grass that is one of the most common grass weeds found in Florida sugarcane. Published by the UF Department of Agronomy, September 2006.